The Effects of Google Word Coach Game and Vocabulary Mastery on Students’ Speaking Skill - Suryadi Suryadi; Winda Widyaningrum; Fajar Erlangga (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The research aims to examine the effects of google word coach game and vocabulary mastery on students' speaking skills. This quasi-experimental study uses a 2x2 nonequivalent control group design with a factorial design carried out in four parallel classes, namely class XI IPS 1, XI IPS 2, XI IPS 3 and XI IPS 4 MA Negeri 1 Serang. Learning outcome data are obtained through pretest and posttest activities. The samples are 80 students randomly taken by adjusting to the condition and aim of the research. The results show a significant difference between the posttest of the experimental group and that of the control group. FO value is 5.225 and Sig. is 0.025 < 0.05. Thus, it shows that the null hypothesis is rejected, and the research hypothesis is accepted. It also means that there is a difference between the interaction effect of Google Word Coach game and that of vocabulary mastery on students’ speaking skills.